337 Falls Pathway and Assessment, an Audit. (16th September 2019) - McCarthy, Kate; Hannon, Evelyn; Carroll, Jennifer
Abstract: Background: Falls remain a common presentation to emergency departments and medical assessment units. They can result in serious injuries requiring surgical intervention and prolonged hospital admission. Conversely a fall may have minimal injury yet still result in prolonged hospital admission. The frailty intervention therapy team (FITT) aims to complete a comprehensive assessment physical and social needs in a time efficient manner. Methods: We reviewed the medical notes of a cross-section of patients, aged over 65 years, on medical wards admitted with a fall. The service, under which, the patient was admitted was noted. We looked at the length of time between admission and physiotherapy review, undertaking bedside tests for postural hypotension and assessment of bone health, with commencement of appropriate therapy pre discharge. We also reviewed medications and if anti hypertensives were stopped or adjusted. Results: Of the 30 patients included, the average length of time from admission to physiotherapy review was 2.6 days. 7 of the patients were seen on the same day, however 3 were awaiting review. Postural blood pressures were requested in one third of the group, predominately in those patients admitted under a geriatric service. A similar pattern was seen in assessment of bone health, although of the patients included, half of them were on at least a single agent for osteoporosis. Conclusion: Development of FITT is of benefit to the health service as a whole and improves early mobilisation, extension for weekend cover should be considered. Interventions such as adjustments to anti hypertensives and opportunistic assessment of bone health should be highlighted to all medical teams. A concise falls pathway encompassing these interventions and FITT assessment does not seem obscure in this age of over-crowding and crisis.